2009
DOI: 10.1161/circresaha.108.190892
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of G Protein–Coupled Estrogen Receptor for Vascular Function and Obesity

Abstract: We found that the selective stimulation of the intracellular, transmembrane G protein-coupled estrogen receptor (GPER), also known as GPR30, acutely lowers blood pressure after infusion in normotensive rats and dilates both rodent and human arterial blood vessels. Stimulation of GPER blocks vasoconstrictor-induced changes in intracellular calcium concentrations and vascular tone, as well as serum-stimulated cell proliferation of human vascular smooth muscle cells. Deletion of the GPER gene in mice abrogates va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
415
3
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(466 citation statements)
references
References 18 publications
27
415
3
9
Order By: Relevance
“…in normal rats, the infusion of G-1 results in an acute reduction in mean arterial blood pressure within 2 min [30]. The effect of G-1 has been confirmed using GPR30 -/-mice.…”
Section: Circulatory Systemmentioning
confidence: 68%
See 1 more Smart Citation
“…in normal rats, the infusion of G-1 results in an acute reduction in mean arterial blood pressure within 2 min [30]. The effect of G-1 has been confirmed using GPR30 -/-mice.…”
Section: Circulatory Systemmentioning
confidence: 68%
“…The effect of G-1 has been confirmed using GPR30 -/-mice. The deletion of GPR30 from mice attenuates the G-1-induced relax of the carotid arteries, and there is no observed sex difference in the reductive effect of GPR30 [30]. The expression of the GPR30 mRNa is observed in the endothelium of the peripheral vessels of Lacz-introduced mice [19].…”
Section: Circulatory Systemmentioning
confidence: 94%
“…35 Role of the novel ER G protein coupled receptor 30 (GPR30) in the cardiovascular system In addition to the two classical ER subtypes, ERa and ERb, a third membrane-bound and G-protein-coupled ER, GPR30, has been identified in human vascular endothelial cells (ECs) and smooth muscle cells. [36][37][38] Haas et al 37 reported that G-1, a selective stimulator of GPR30, acutely blocked vasoconstrictor-induced changes in intracellular calcium concentrations and vascular tone, resulting in lowering of blood pressure in normotensive rats. Similar vasodilator effects of GPR30 have been confirmed in other studies.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 99%
“…[39][40][41] It has also been reported that stimulation of GPR30 blocks VSMC proliferation. 37,42 The vasodilator action of G-1 may be mediated by NO-independent 40 and NO-dependent 37,39,40 pathways; the latter involves GPR30-induced endothelial NO synthase (eNOS) phosphorylation. 43 Also, G-1 decreases nicotinamide adenine dinucleotide phosphate-stimulated superoxide production by the carotid and intracranial arteries, indicating the scavenging effects of GPR30 on superoxide anions.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 99%
“…The effect of PMCA4b to promote GPER/ GPR30-mediated ERK1/2 phosphorylation likely plays a role in the initiation of more long term or genomic outcomes of GPER/ GPR30 activation. In addition, GPER/GPR30 agonist G-1 has been shown to acutely trigger Ca 2ϩ signals (50,51). In many cases, these Ca 2ϩ signals were used as a parameter of receptor activation (2,3,16).…”
mentioning
confidence: 99%